Some Properties of the Members of Petersen Family - Israa M. Tawfik (Tikrit Journal of Pure Science)
This article has restudied the Petersen family in Graph Theory. It discussed the process of establishing this family. This discussion leads to discovering some new properties of the Petersen family's members.